Optimization of watermelon waste as a bulking agent for sustainable co-composting of livestock manures using response surface methodology - Nurin, Arifah Yusoff; Tee, Tuan Poy; Chin, Nyuk Ling; Zainudin, Mohd Huzairi Mohd; Nayan, Nazri (Frontiers in Sustainable Food Systems, 2024)
Global human population growth has resulted in significant intensive agricultural activity, posing substantial challenges to waste management and environmental conservation. Watermelon waste (WW), chicken manure (CM) and horse manure (HM) are among the main contributors to agricultural waste due to their abundant waste production. This study aims to manage the daily production of these wastes by utilizing WW as a bulking agent in the co-composting of CM and HM. Response surface methodology (RSM) was employed to analyze the effects of four independent factors: HM:CM composition, particle size, composting period, and bulking agent amount. Thirty treatments were developed using central composite design and in-vessel composting reactors were employed to study the relationship between the factors involved and compost physicochemical quality parameters. The results demonstrated significant effects on organic matter (OM), nitrogen (N), potassium (K), dry matter, moisture content, bulk density, and pH, while the carbon-to-nitrogen ratio (C/N) and phosphorus level were not affected. The optimized co-composting conditions obtained from RSM were 75:25 for HM:CM composition (%), 0.5 cm for particle size, 40 days for composting period, and 10% of WW, resulting in a compost with 61% OM, 2.5% N, and 2.5% K. These optimal conditions agreed closely with the predicted values; root mean square prediction error (RMSPE) was less than 0.50, revealing the success of RSM in determining optimal process parameters and developing models for predicting responses. Our study demonstrated that WW as a bulking agent in the co-composting of CM and HM has significantly enhanced the organic matter and nutrient levels of the final compost product.